Ecology of Indian Crested Porcupine (Hystrix indica) in and around Jodhpur, Rajasthan - Ojha, Aazad P.; Rajpurohit, L. S. (Indian Forester, 2018)
Western Rajasthan is the mixture of an arid and semi-arid region, which has a huge desert called 'The Great Indian Thar desert'. It is rich in biodiversity and comprises many unique endemic species. Indian crested porcupine is monogamous species, which is nocturnal and herbivore. The study area of the porcupine is unique and it is present in west part of Jodhpur city. Our study areas included 'Bhooteshwar Van Khand' (Forest area), outside west part of Jodhpur city wall lies in a semi-arid region where different behavior (burrow, feeding, breeding etc) and other activity of ICP were studied. During the study, it is found that change in behavior and activity of porcupine is mainly due to anthropological factor, which makes them survive in this conditions. Road accident and predation by dogs are the major threat to their population in this area. Detail study is needed to study the effect of food preference habit and interspecific interaction with the human.